Social transfers and growth: The missing evidence from luminosity data - Juan M. Villa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
The effects of social transfers on growth are still unclear. The limitations of aggregated data at sub-national levels have confined the analysis to the use of simulation models and household surveys. As an alternative, this paper contributes to the empirical literature by assessing the effects of Colombia's Familias en Accion, a human development cash transfer programme, on municipality level growth rates during its initial stage of implementation between 2000 and 2004. The natural experiment that resulted from the scaling-up of the intervention facilitated the set-up of a difference-in-differences analysis. The lack of sub-national GDP accounts is tackled by using luminosity data generated by satellites orbiting the earth, which have demonstrated to be a suitable proxy for economic growth and per capita growth. The results show that the programme can generate large positive effects on municipality level economic growth rates. Robustness checks confirm the reliability of these findings.
Keywords: I38; O10; R10; 330; social transfers; economic growth; local economy effects; Familias en Accion; difference-in-differences treatment effects